Statistical Distribution of Si Phases at Different Sr Levels in AlSi9 Alloys - Kalkan, Ibrahim Halil; Hizli, Ibrahim Goksel; Dizdar, Kerem Can; Kahruman, Cem; Dispinar, Derya (Springernature, 2024)
Al-Si alloys are widely used in many automotive applications. Mechanical properties of this alloy group strongly depend on the size, shape, and distribution of silicon phase. Therefore, Sr is added to alloy to alter the needle-like shape to fibrous morphology in order to achieve higher fluidity, increase feedability, decreased porosity, and high mechanical properties. In this work, the effect of strontium modification on the AlSi(9 )casting alloy were studied in detail. From 0 to 600 ppm, strontium was added to AlSi9 casting alloy and microstructural changes were evaluated. Metallographic characterization carried out on each sample and size and distribution of Si phase was analyzed by image analysis tools. Texture and pore figures were analyzed by EBSD.
Keywords: Strontium modification; Aluminium alloys; Metallography; Silicon; Statistics